PENGARUH LOKASI, KUALITAS PELAYANAN, FASILITAS DAN SUASANA LINGKUNGAN TERHADAP KEPUASAN PENGUNJUNG KEBUN RAYA BOGOR - Bakti, Rizal; Oktafiani, Nadya (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2019)
Bogor Botanical Gardens is a natural tourist attraction in the city of Bogor which has a variety ofex-situ plants as its appeal. The number of domestic and foreign tourists visiting the BogorBotanical Gardens experienced a fluctuating development, It’s expected to improve the quality andquality of services and facilities that remain to be maintained.The result of regression test showsthat 75,1% of visitor satisfaction factors can be explained by location, service quality, facilities, andvisitor's ambience while the rest 24,9% is explained by other factors not examined in this research.While the result of F test shows that simultaneously location variable, service quality, facility, andvisitor atmosphere simultaneously have positive and significant effect to visitor satisfaction withresult of analysis that is Fcount = 75,460> Ftabel = 2,460. The result of T test shows that the locationvariable shows the result of analysis tcount(2.044), quality of service ttable (2,236), ttable facility (2,678)and transient environment (3,036) where ttable (1,985), partially all variable have positive andsignificant effect to satisfaction Visitors Bogor Botanical Garden.The variables that dominate thevisitor satisfaction of Bogor Botanical Gardens are the environment of atmosphere.